Algoritmich societies and processes of subjectivation: The rise of new forms of power? - Chece, Diego Maria (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this article is to indagate the profound changes of the human environments, which arising from the “Digital revolution”. In the first part, the author compares two “ontological” perspectives: respectively, the “Infosphere” and the “Docusphere”. Afterward, taking into account the contemporary processes of subjectivation, he distinguishes between two emerging patterns of political power: “Surveillance capitalism” and “Societies of control”. In the light of the distinction between surveillance and control, the author discusses the elements of each pattern which seem to be useful for understanding the political life in digital societies.